Penerapan Teknik SEO Untuk Peningkatan Potensi Pemasaran Peralatan Pemadam Kebakaran - Angela Woen; Chatrine Sylvia; Fandi Halim (STMIK Royal, 2022)
Abstract: Sinar Jaya store is a store that sells fire extinguishers in Medan city. In majority, this store still serves transactions by accepting customer to the store directly. Since the COVID-19 pandemic has lasted for so long, this store has begun to explore technology by utilizing Instagram as social media and having a website which can be accessed via www.sinarjayamedan.com as a medium to introduce the store, market the products digitally and increase business legitimacy. However, existing web pages must be optimized further to improve the ability of Toko Sinar Jaya in response to marketing needs. The measurement results using 2 (two) Search Engine Optimization (SEO) measurement websites show an average score of 61,5 out of a scale of 100. Thus, this community service activity is aimed at increasing this SEO score. SEO activities are carried out by using the on-page SEO method on existing web pages and continued with Content Management training for off-page SEO implementation. On-page SEO is carried out with activities including the installation of the Yoast SEO plugin, keyword research, visibility and permalink settings, Google Search Console, Google Analytics, sitemap generator and schema markup. The SEO score then increased significantly from 61,5 to 74,5. Keywords: inbound marketing; micro, small and medium enterprise; search engine optimization (SEO) Abstrak: Toko Sinar Jaya merupakan toko yang menjual alat-alat pemadam kebakaran di kota Medan. Secara mayoritas, toko ini masih melayani transaksi langsung dengan menerima kedatangan pelanggan ke toko. Sejak pandemi COVID-19 yang berlangsung telah begitu lama, toko ini mulai mengeksplorasi teknologi dengan memanfaatkan media sosial Instagram dan memiliki website yang bisa diakses lewat www.sinarjayamedan.com sebagai media untuk memperkenalkan toko, memasarkan produk secara digital dan meningkatkan legitimasi bisnis. Namun demikian, laman web yang ada harus dioptimalkan lagi untuk lebih meningkatkan kemampuan Toko Sinar Jaya dalam menjawab kebutuhan pemasaran. Hasil pengukuran menggunakan 2 (dua) website pengukuran Search Engine Optimization (SEO) masih menunjukkan rata-rata skor 61,5 dari skala 100. Kegiatan pengabdian kepada masyarakat ini ditujukan untuk meningkatkan skor SEO ini. Kegiatan SEO dilakukan secara on-page terhadap laman web dan dilanjutkan dengan pelatihan Content Management untuk implementasi SEO secara off-page. SEO on-page dilakukan dengan kegiatan meliputi Instalasi plugin Yoast SEO, keyword research, visibility and permalink setting, Google Search Console, Google Analytics, sitemap generator dan schema markup. Skor SEO kemudian meningkat dengan cukup signifikan dari angka 61,5 menjadi 74,5. Kata kunci: inbound marketing; search engine optimization (SEO); usaha mikro, kecil dan menengah (UMKM)